La violación de los derechos humanos de las personas privadas de la libertad al continuar el hacinamiento en los centros de privación de la libertad, necesidad de agregar un inciso en el art. 4 del código orgánico integral penal - Riofrío Briceño, Wilson Rodrigo (2017)
The State is the representation of each and every citizen through an abstract, comprehensive and lasting institution beyond time, whose action is through the organization of its components, ie citizens, to fulfill this purpose, the state requires institutions that hierarchically systematic and coordinated actions for the protection of rights and fulfillment of obligations and citizens. Part of this institutional framework consists of the right, which is a set of standards or rules that must be followed by each Member State, regardless of status, race, sex, ethnicity or nationality, this comes a branch which is composed of criminal law, which essentially aims to prevent the commission of harmful actions towards social stability, rights and citizens in general the collective order, inflicted the provisions of the law pitifully proceeds to penalize infringements or offenses committed by persons individually or collectively. As part of the system sanction the commission of offenses or crimes, deprivation of liberty law was established as a restriction mechanism of this universal right of humanity, in order to raise awareness in each of the citizens, to respect and order both individually and collectively, and the case of a breach pose and respects the provisions, through the application of due process, restrict this right for a period of time determined by the competent authorities and in turn submit to violator to a process of re-education and social rehabilitation. Is that this research is based on the problem of prison overcrowding that exists today in our country, also known as prison overcrowding, ie excess or overpopulation of individuals within social rehabilitation centers nationwide, situation that not only impedes the process of -reinserción social rehabilitation, also affects the physical and psychological health of persons deprived of their liberty, for this reason we will proceed to make a conceptual, doctrinal, legal and legal collection compared, with the aim of establish the main aspects inherent to the treated problem from its origins up to obtaining the corresponding conclusions, recommendations and, above all, the proposed legal reform provide a solution that allows both technical and legal and administrative to prison overcrowding.